The experiences of recently diagnosed HIV-positive individuals, as shared on an online forum - Wylde, Charlotte Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 2018)
An HIV-positive diagnosis can be an overwhelming and traumatic experience. This study explores the experiences of receiving an HIV-positive diagnosis. Employing an Interpretative Phenomenological Analysis (IPA), a sample of the initial posts from threads on an online forum, was collected and explored, in order to determine the dominant themes from the experiences expressed in the posts, as well as the support sought from the forum. The online forum was accessed as an unobtrusive observer, and posts from January to December 2015 were explored. The online forum provides a platform for disclosure following an HIV-positive diagnosis, when anxiety and fear of stigma can impact on an individual's ability to disclose to their social support network of family and friends. The experiences expressed on the online forum reflect the emotional, mental and physical impact of an HIV-positive diagnosis on an individual. The findings in this study reflected themes of shock, guilt and hopelessness, and concerns and fears regarding disclosure and stigma associated with HIV, as well as the importance of social support for the coping mechanisms of individuals after receiving an HIV-positive diagnosis. This research demonstrates the importance of Internet accessibility for information and support for chronic illnesses, such as HIV, and the role of the online forum platform for providing a safe environment for individuals recently diagnosed HIVpositive.
Keywords: HIV-positive persons -- Social networks; HIV infections -- Diagnosis -- Psychological aspects; HIV infections -- Social aspects; HIV infections -- Electronic discussion groups; Internet -- Social aspects; Stigma (Social psychology); Phenomenological psychology